Pathways of interest and participation: How STEM‐interested youth navigate a learning ecosystem. Issue 4 (3rd May 2021) - Shaby, Neta; Staus, Nancy; Dierking, Lynn D.; Falk, John H.
Abstract: Despite considerable efforts in recent years to encourage Science, Technology, Engineering and Mathematics (STEM) interest and participation among youth, STEM interest during adolescence continues to decline. Recently, researchers, educators, and policymakers have used a learning ecology perspective to better understand the development and persistence of youth interest in STEM topics or activities. This study examined the dynamics of the STEM interest and participation pathways of three youth in an under‐resourced, urban community. These three cases offer insights into how youth with a strong interest in a STEM topic or activity perceived the resources that were available to them in a STEM learning ecosystem and highlight the affordances and constraints each faced in pursuit of their interests. We interviewed each youth 4–5 times during their middle school and high school years (ages 11–14). The analysis reinforces the unique nature of youth interest pathways, but also common factors that contributed to each of these pathways. The ability of youth to navigate the ecosystem depended on the availability and accessibility of both in‐ and out‐of‐school learning resources related to their interest, and the support they received from significant adults in their lives in terms of both social, cultural, and financial capital. This study offers important insights into how STEM learning ecosystems might best be structured to enable more youth to develop strong, enduring interests in STEM.